RESPONSIVITAS PEMERINTAH KOTA DUMAI TERHADAP LIMBAH B3 DI SUNGAI SEMBILAN KOTA DUMAI TAHUN 2017-2018 - Nasution, Muazzoful Khalili; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Industrial activities produce a variety of environmental wastes, the most hazardous waste to the environment and health is waste that is categorized as toxic hazardous waste. B3 waste pollution can be through land, water, or air. The pollution causes environmental degradation. Industrial development not only has a positive impact but also a negative impact, namely in the form of industrial waste which if not managed properly and correctly will disturb the environmental balance. Then how about responsiveness and inhibiting factors of the Dumai City Government in B3 waste pollution in the Sembilan river. The purpose of this study was to determine the responsiveness of the Dumai City Government in tackling B3 waste pollution in the Sembilan river and to find out what are the factors that inhibit the Dumai City Government in tackling the B3 waste pollution in the Sembilan river. The research method uses a qualitative approach to the type of descriptive research. The results of this study are the Government of the City of Dumai itself has not been able to solve the problem of B3 waste that is in the Sembilan City river, because of the gaps in the city of Dumai as a technical institution not having the ability to execute, plus incomplete infrastructure and lack of human resources skills. the factors which hamper this waste management are the limited budget, facilities and infrastructure and human resources that are not comparable with the volume of waste, as well as the lack of community participation not to litter. Keywords: Responsiveness, B3 waste